Eicosapentaenoic Acid and Docosahexaenoic Acid Differentially Modulate Monocytes in Chronic Inflammation: A Randomized Clinical Trial - So, Jisun. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Stefania Lamon-Fava.; Committee: Alice Lichtenstein, Dayong Wu, and Albert Tai.; Keywords: Nutrition, Immunology, and Cellular biology.